Modeling the Market Fluctuations of Ammonia Price - Isella, Andrea; Manca, Davide (Computer Aided Chemical Engineering, 2024)
The fertilizer industry is one of the most prominent sectors of chemical engineering and manufacturing: by way of example, it generates in the United States of America more than USD 155 billion in economic revenues annually and provides more than 495,000 jobs (The Fertilizer Institute, 2022). Indeed, since half of all food grown worldwide today is made possible through fertilizers, and, as demand continues to increase, their role will only become more important as a key ingredient in feeding a rising global population. Among fertilizers, ammonia is the primary reference compound, as it represents the raw material for the vast majority of their manufacturing and shows the highest production volumes (Isella and Manca, 2022). Based on the previous, pioneering works of Manca (2013, 2015, 2016) on commodity price forecasting, this paper presents a systematic approach to predict the evolution of the ammonia price in the next years for the feasibilitystudy framework of dynamic conceptual design. Specifically, different autoregressive models are proposed to forecast the distribution of (i) commodity prices that contribute to the definition of the ammonia price and (ii) the ammonia price itself.